2014
DOI: 10.15361/1984-5529.2014v42n3p271-277
|View full text |Cite
|
Sign up to set email alerts
|

Vigor e produção de sementes de crambe tratadas com fungicida, inseticida e polímero

Abstract: ResumoO objetivo do trabalho foi determinar a eficiência do tratamento químico de sementes de crambe com fungicida, inseticida e polímero na qualidade fisiológica e na produção de sementes. Sementes de crambe, cultivar FMS brilhante, foram submetidas aos seguintes tratamentos: T1 = Testemunha; T2 = Fungicida (F); T3 = Inseticida (I); T4 = Polímero (P); T5 = F + I; T6 = F + I + P; T7 = F + P, e T8 = I + P. O fungicida utilizado foi o Derosal 500 SC (i.a. Carbendazim), na dose de 3,0 ml kg -1 de sementes, e inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
1
3
0
5
Order By: Relevance
“…The control presented higher values when compared to the other treatments. These results corroborate Ludwig et al (2014) who suggests that these results are due to phytotoxic effect of the higher concentration of the chemical on the germitest paper during the initial growth of the seedling.…”
Section: Resultssupporting
confidence: 90%
“…The control presented higher values when compared to the other treatments. These results corroborate Ludwig et al (2014) who suggests that these results are due to phytotoxic effect of the higher concentration of the chemical on the germitest paper during the initial growth of the seedling.…”
Section: Resultssupporting
confidence: 90%
“…In this case, it is possible that the chemical treatment caused a phytotoxic effect on the initial seedling growth, as mentioned by Ludwig et al (2014) in sowing of cambre seeds, using the substrate filter paper, in which the coating of chemically treated seeds with polymers, potentiated the action of the insecticide and fungicide causing damage to germination under laboratory conditions. Averages not followed by the same letter in the column, differ by the Scott-Knott test at the 5% probability level.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth highlighting that uncoated seeds from the control treatment presented 17.5% of seedlings infested with fungi ( Figure 2C). Ludwig et al (2014), studying the strength and production of crambe seeds treated with fungicide, insecticide and polymer, concluded that the application of fungicide and/or insecticide associated or not to the polymer, affected the strength of the seed in laboratory tests, but in soil conditions, it did not affect germination and emergence of crambe seedlings. Table 2.…”
Section: Laboratorymentioning
confidence: 99%
“…Under greenhouse conditions, the negative effect of fertilizer on the coating is significantly reduced, probably due to the dilution of the coating compounds by the irrigation during the period of this experiment and also because of the adsorption and leaching of part of the compounds. An option to minimize the problems could be the reduction of fertilizer doses as well as the amount of inert material that is used on the coating (Ludwig et al, 2014).…”
Section: Greenhousementioning
confidence: 99%